Procedimiento de certificación de discapacidad de la Secretaría de Salud del Municipio de Cereté (2023)
People with disabilities experience significant health inequalities compared to people without disabilities. In this area of work, PAHO seeks to improve health equity and the inclusion of the health system for persons with disabilities in line with the main regional and global human rights frameworks. (Health, s.f.) The country's disabled population today can access a comprehensive medical assessment of their disabling condition. The multidisciplinary teams of health professionals from the Health Service Provider Institutions –IPS– authorized by the Departmental or District Health Secretariats are in charge of carrying out this function. (social, minsalud, s.f.) Given this, the health secretary of the municipality of Cereté has the disability certification process for all those people who have difficulties in their normal development, however, they do not have this process in a documented manner, therefore, Through review of bibliographies on the subject and support from officials in this area, the certification procedure was documented, to facilitate access to information on the step-by-step requirements to obtain the certificate. On the other hand, in the analysis of the disability certification process, the importance of the disability certificate was made known and what benefits or programs they can access, followed in the deployment of the disability certification procedure, it has a presentation, objective, scope and in detail of the step by step to obtain the certificate of disability and ends with the socialization of the documentation to the officials of the secretary of health of the mayor's office of the municipality of cereté.